Social and solidarity economy and the need for its entrepreneuring ecosystem: Current challenges in Brazil - Morais, Leandro Pereira [UNESP]; Bacic, Miguel Juan (Universitat de Valencia, 2020)
This articles purpose is to discuss the state of the art of the constitution of the entrepreneurial ecosystem for SSE and its application in Brazil. One of the major challenges for the creation, continuity and strengthening of Solidarity Economy Enterprises (SEE) is the effective establishment of an entrepreneurial ecosystem for Social and Solidarity Economy (SSE). The construction of the solidary entrepreneurial ecosystem is a complex task, full of challenges, especially when this construction is associated to structural weaknesses inherent to its modus operandi. Case studies of several countries allow us to define general guidelines for the application of public policies that show paths in this direction. Considering this, we organized the article as follows: After the Introduction, we discuss some aspects of the entrepreneurial ecosystem, in topic 1. Then, topic 2 presents the idea of the triple helix and coevolution among the elements of the ecosystem and enterprises. Next, topic 3 addresses the construction of the entrepreneurial ecosystem for SSE in some countries in Europe and Asia. Finally, in item 4, some considerations about the Brazilian case.
Keywords: Co-evolution; Social and solidarity economy; Solidarity economy enterprises; Solidarity entrepreneurial ecosystem